1995
DOI: 10.1113/jphysiol.1995.sp020610
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by zinc ions of native rat and recombinant human inhibitory glycine receptors.

Abstract: 1. The effect of the divalent cation Zn2+ on inhibitory glycine receptor (GlyR) currents was investigated in rat embryonic spinal cord neurons and Xenopus oocytes expressing recombinant GlyRs.2. In cultured spinal neurons, Zn2+ potentiated glycine-induced whole-cell currents about 3-fold when applied extracellularly at concentrations of 0-5-10 /LM. In contrast, higher concentrations (> 100 /M) of Zn2+ decreased the glycine response. 3. A similar biphasic modulation of glycine-induced currents by Zn2+ was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
159
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(178 citation statements)
references
References 18 publications
(28 reference statements)
19
159
0
Order By: Relevance
“…As demonstrated previously, the ␣ WT GlyR is highly sensitive to zinc inhibition. As expected from previous studies employing mutations at these positions (7,15,16,29), none of these mutations had dramatic effects on the glycine EC 50 , n H , or I max values. The inhibitory zinc dose responses for the ␣ H107A GlyR, the ␣ H109A GlyR, the double mutant ␣ H107A,H109A GlyR, and the co-expressed (␣ H107A ϩ ␣ H109A ) GlyR were measured in the presence of an EC 20 glycine concentration.…”
Section: Homology Modeling Indicates That Hissupporting
confidence: 59%
See 1 more Smart Citation
“…As demonstrated previously, the ␣ WT GlyR is highly sensitive to zinc inhibition. As expected from previous studies employing mutations at these positions (7,15,16,29), none of these mutations had dramatic effects on the glycine EC 50 , n H , or I max values. The inhibitory zinc dose responses for the ␣ H107A GlyR, the ␣ H109A GlyR, the double mutant ␣ H107A,H109A GlyR, and the co-expressed (␣ H107A ϩ ␣ H109A ) GlyR were measured in the presence of an EC 20 glycine concentration.…”
Section: Homology Modeling Indicates That Hissupporting
confidence: 59%
“…Several lines of evidence suggest that the glycine receptor chloride channel (GlyR), 1 which mediates inhibitory neurotransmission in the spinal cord and brainstem (6), may be a physiological target for zinc modulation. First, zinc exerts potent effects on the GlyR; low concentrations (0.01-10 M) potentiate glycinergic currents by increasing the apparent glycine affinity, whereas higher concentrations (Ͼ10 M) inhibit the current by reducing the apparent glycine affinity (7). Second, an ultrastructural study has found evidence for zinc and glycine co-localization in individual presynaptic terminals in the spinal cord (8).…”
mentioning
confidence: 99%
“…For heterologous expression of NR1/NR3A receptors, 25 ng of cRNA was injected at an NR1/NR3 ratio of 1:2 into Xenopus laevis oocytes. Oocytes were isolated and maintained as detailed previously (36). Two-electrode voltage clamp recording of whole-cell currents was performed at holding potentials of Ϫ70 mV according to Laube et al (36).…”
Section: Methodsmentioning
confidence: 99%
“…For example, zinc depresses I gly in rat cerebellar granular cells (Virginio and Cherubini 1997) and rat septal cholinergic neurons (Kumamoto and Murata 1996). However, zinc modulation of I gly in rat embryonic spinal cord, human GlyR ␣1 and GlyR ␣2 expressed in HEK 293 cells and Xenopus oocytes (Bloomenthal et al 1994;Laube et al 1995) and isolated retinal cells (Han and Wu 1999) is bidirectional, eliciting facilitation and depression depending on the zinc concentration.…”
Section: Zinc Modulation Of Hippocampal Glyrsmentioning
confidence: 99%
“…Several studies show that GlyRs in forebrain regions are modulated by zinc. For example, zinc depresses I gly in cerebellar neurons (Virginio and Cherubini 1997) and septal cholinergic neurons (Kumamoto and Murata 1996), but bidirectionally modulates (facilitates as well as depresses) I gly , depending on the zinc concentration, in spinal cord neurons (Bloomenthal et al 1994;Laube et al 1995) and retinal ganglion cells (Han and Wu 1999). We sought to determine whether native GlyRs in hippocampus are modulated by zinc and to investigate whether the modulation of I gly by zinc is similar or different to the well-characterized zinc modulation of I NMDA .…”
Section: Bidirectional Modulation Of Hippocampal Glyrs By Zincmentioning
confidence: 99%